Increasing meal consumption in individuals with competing protective equipment. (19th July 2019) - Fleck, Chelsea R.; Bourret, Jason C.; Lloveras, Lindsay A.
Abstract : Individuals diagnosed with autism spectrum disorder may engage in self‐injurious behavior that can cause tissue damage. Protective equipment is sometimes used to decrease the severity of tissue damage when self‐injury occurs. However, wearing protective equipment may be incompatible with some forms of adaptive behavior, such as meal consumption. The purpose of the present analysis was to identify a treatment for increasing meal consumption in two adolescent males diagnosed with an autism spectrum disorder who wore protective equipment that interfered with self‐feeding. Three interventions were evaluated: modifying the protective equipment, manipulating the reinforcing efficacy of the meal, and arranging additional positive reinforcement for meal consumption in the absence of protective equipment. Modifying protective equipment and manipulating the reinforcing efficacy of the meal were effective for both participants. Additional positive reinforcement was evaluated and effective for one participant.